Nilai-nilai Pendidikan Islam dalam Buku “Stop Pacaran, Ayo Nikah!” Karya Hamidulloh Ibda - Wiwin Nur Hidayah (Institut Islam Nahdlatul Ulama Temanggung, 2020)
The purpose of this study was to determine the values ​​of Islamic education contained in the book Stop Dating for Marriage! Hamidulloh Ibda's work and the implications of the value of Islamic education in the book Stop Dating Come Married! towards adolescent behavior. This research is included in the type of library research, while the method used is descriptive qualitative method. Data collection techniques in this study using recording techniques or document review. The results of the discussion conducted on the book Stop Dating Let's Get Married! namely knowledge about the nature of dating in adolescent life and the concept of marriage and marital relations. The values ​​of Islamic education contained in this book are the values ​​of i'tiqadiyyah, khuluqiyyah, amaliyah, and education to protect offspring. From the analysis conducted by the researchers found the values ​​of Islamic education implicit in this book are the need to gather the intention and determination to establish relationships to dare to justify it; i'tiqadiyyah values ​​such as faith in God and faith in the destiny of God; Amaliyah values ​​such as behaving humbly or not arrogant, always covering genitalia, sincerity, Husnudzon, and having good manners; syakhsyiyah values ​​such as justifying the relationship with marriage, running the sunnah by getting married and building a sakinah mawadah warahmah family; the value of education to protect offspring (hifdzal-nasb), ie to avoid adultery so that their offspring are awake. The implications of the values ​​of Islamic education in the book are knowing the nature of courtship in Islam, applying the values ​​of Islamic education, inviting the application of Islamic education values ​​and being an example for other teenagers. Conclusion from the book Stop Dating Let's Get Married! Hamidulloh Ibda's work, a young man must have the courage to justify his love within the frame of marriage, not to civilize courtship